2003
DOI: 10.1046/j.1360-0443.2003.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Reasons for Smoking Scale: factorial structure, gender effects and relationship with nicotine dependence and smoking cessation in French smokers*

Abstract: The questionnaire yielded a coherent factor structure; women smoked more for tension reduction/relaxation, stimulation and for social reasons than men; addictive smoking and automatic smoking behaviour were similar in both sexes and were associated strongly with a high level of nicotine dependence; the 'habit/automatism' score predicted failure to quit over and above cigarettes per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
124
3
29

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(181 citation statements)
references
References 28 publications
(47 reference statements)
24
124
3
29
Order By: Relevance
“…Pragmatically tobacco consumption negatively reinforces the smoking habit (Zvolensky and Schmidt, 2003;Ozturk, et al, 2011). Further previous studies found that depression, stress, anxiety, stimulation and socialization are the precipitating factor for smoking cigaretteamong adults (Berlin et al, 2003;Leventhala et al, 2013), but the present study could not find these are the factors predict the smoking cigarette among students in Malaysia. Inadequate knowledge about nicotine dependency and its consequences of smoking cigarette (Al-dubai et al, 2012), and irrational belief that smoking reduces the psychological distress are most likely cause to smoke cigarette among students.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Pragmatically tobacco consumption negatively reinforces the smoking habit (Zvolensky and Schmidt, 2003;Ozturk, et al, 2011). Further previous studies found that depression, stress, anxiety, stimulation and socialization are the precipitating factor for smoking cigaretteamong adults (Berlin et al, 2003;Leventhala et al, 2013), but the present study could not find these are the factors predict the smoking cigarette among students in Malaysia. Inadequate knowledge about nicotine dependency and its consequences of smoking cigarette (Al-dubai et al, 2012), and irrational belief that smoking reduces the psychological distress are most likely cause to smoke cigarette among students.…”
Section: Discussioncontrasting
confidence: 93%
“…The present study found that nicotine dependency or addiction is one of the major precipitating factor predicts smoking cigarette behaviouramong students than tension and pleasure, but smokers believe and justify that smoking cigarette reduce their tension, enhance their pleasure, facilitate to cope with stress, socialize with others and relax their mind (Berlin et al, 2003;Fidler and Wesr, 2009;Souza et al, 2010;Hock et al, 2014). Pragmatically tobacco consumption negatively reinforces the smoking habit (Zvolensky and Schmidt, 2003;Ozturk, et al, 2011).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The MRSS (Berlin et al, 2003) was used to assess RS. The scale consists of 21 items rated on a five-point Likert scale with anchors of one (never) to five (always).…”
Section: Reasons For Smokingmentioning
confidence: 99%
“…The Modified Reasons for Smoking Scale (MRSS; Berlin et al, 2003) been validated with several international samples (Berlin et al 2003;Boudrez & De Bacquer, 2012;Souza, Crippa, Pasian, & Martinez, 2009), but has not yet been validated with a U.S. sample. Therefore, a secondary goal of the study was to evaluate the factor structure of the MRSS among a U.S. sample.…”
mentioning
confidence: 99%